Suitors and sabotage - Anstey, Cindy (New York : Swoon Reads, 2018)
1817 Kent, England. Imogene Chively's father has chosen Ernest Steeple as her future husband. But his younger brother, Benjamin, wins her heart while she is giving him drawing lessons. When a series of accidents threaten the pair, it becomes evident that someone seeks to do Ben harm.
Keywords: Courtship -- Juvenile fiction; Romance fiction; Tutors and tutoring -- Juvenile fiction; Artists -- Juvenile fiction; Families -- England -- Juvenile fiction; Young adult fiction; Courtship -- Fiction; Love -- Fiction; Tutors and tutoring -- Fiction; Artists -- Fiction; Family life -- England -- Fiction; YOUNG ADULT FICTION -- Historical -- Europe; YOUNG ADULT FICTION -- Romance -- Clean & Wholesome; YOUNG ADULT FICTION -- Romance -- Historical; Courtship; Families; Romance fiction; Tutors and tutoring; Young adult fiction; Fiction; Historical fiction; History; Juvenile works; Novels; Young adult works; Historical fiction; Novels; Teen fiction